Bringing Personal Character Strengths into the Production of the Leisure Experience. (14th March 2016) - Coghlan, Alexandra; Filo, Kevin
ABSTRACT: This study explores opportunities for character strength activation through the leisure context of charity sport events. Character strengths are a core aspect of positive psychology, and their activation increases wellbeing. Based on a card sorting procedure and semi-structured interviews, respondents identified which strengths they used during charity sport event participation. Results indicate that kindness/generosity, citizenship, loyalty and teamwork, hope and optimism, and passion and enthusiasm were all core event-related strengths. The findings provide insights regarding the relationship between leisure participation and wellbeing, as we know that (i) leisure frequently leads to increased wellbeing, (ii) this leisure context provides an opportunity to activate specific character strengths, and (iii) these specific character strengths are known to increase wellbeing. Therefore, it may be that the activation of these event-specific character strengths provides a mechanism to derive wellbeing outcomes from leisure participation, and should be further explored in the design of charity sport events.